Lan network analysis in tsanawiyah al-kahfi madrasah palembang - Nur Kholisah Nur Kholisah; Jimmie (International Journal Cister, 2022)
Advances in information technology are currently growing in line with human needs who want convenience, speed and accuracy in obtaining information. Therefore, the advancement of Information Technology must continue to be pursued and improved in quality and quantity. One of the advances in information technology in the field of transmission that is currently developing in addition to fiber optics is the use of Local Area Network (LAN) devices. This Local Area Network device allows for the relationship of information users even when they are mobile (moving), thus, providing convenience for information users in carrying out their activities. One example of its application is the use of mobile phones. The general network term heard today is LAN.